Isolation and identification of tropical source Lactobacillus plantarum CK3 and its effects on fatty liver in laying hens - Yongzhen Chen; Xinyu Feng; Xinyi Zhang; Andrea Abreo Medina; Jiayu Feng; Xin Li; Meiyu Duan; Yawei Qiu; Fang Gan (Research in Veterinary Science, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Hysteretic behavior of reinforced ultra-high-performance concrete columns under combined axial and flexural loads - Qiwu Wang; Zhi Fang; Wenjie Zheng; Fei Peng; Yawei Fang; Jiaxing Chen; Hua Huang (Bulletin of Earthquake Engineering, 2026)

Chloride Loss in Fine Aerosols over the Atmosphere of Pearl River Estuary - Yuan Gao; Jianbo Ye; Lili Ming; Run Lu; Jiayin Sun; Guizhen Fang; Yawei Xue; Yee Jun Tham (Aerosol Science and Engineering, 2026)

Novel enhanced network integrating transformations of DOM and microorganisms (ENITM) elucidates microbial-driven transformation pathways in estuarine sediments - Shiyang Yu; Jitao Lv; Xindong Ma; Lu Jiang; Qiurui Zhang; Tianyu Chen; Han Fang; Dong Cao; Lixia Zhao; Yawei Wang (Water Research, 2026)

Cross-cultural consumer acceptance of sustainable protein-rich foods; legumes, plant-based meat analogues and hybrids, and cell-based foods - Isabella Tao Jakobsen; Marleen C. Onwezen; Yawei Wang; Fang Zhong; Derek Victor Byrne; Barbara Vad Andersen (Food Quality and Preference, 2026)

Morphological and functional analysis of saccus vasculosus of mandarin fish ( Siniperca chuatsi ) - Rahma Sakina Said Aly; Jiajie Fang; Keying Li; Xiao Ma; Jiong Gao; Meng Zhang; Xiaowu Chen; Yawei Shen (Journal of Fish Biology, 2026)
The saccus vasculosus (SV) is a specialized periventricular organ found in some species of teleost and elasmobranch fishes, located at the back of the hypothalamus and pituitary gland. However, its function remains incompletely understood. In this study, histological, transmission electron microscopy (TEM) and transcriptomic analyses were employed to investigate the SV of the mandarin fish ( Siniperca chuatsi ) to gain insights into its morphology, gene expression profile and function. Through histological staining techniques, different cell types within the SV can be identified and characterized. The SV is highly folded vascularized neuroepithelium and is deeply connected to blood vessels. TEM studies showed that the capillaries that produced the lumen formed complex narrow channels are linked to the third ventricle of the hypothalamus. The bright neuroepithelium is formed by coronet cells and supporting glial cells, interspersed with liquor‐containing neurons, while the dark contrast is attributed to the presence of heavy elements such as calcium. We identified 28 specific genes in SV, which are most enriched in the purine metabolism pathway, including the genes of pde9al , pde9ac , pde6hl and sgc88el . Gene Ontology biological process analysis for the SV‐specific genes showed that response to osmotic stress was the hub term according to the enrichment maps. Additionally, SV‐specific genes opsin ( opsin8b ), photoreceptor ( pcare1 ) and aquaporin ( aqp4 , aqp9l ) of Siniperca chuatsi may indicate that they play a role as a sensor of season and are involved in osmoregulation. This study, the first on the Siniperca chuatsi , suggests that the SV may have unique physiological functions in teleost fish.

Ceramic ultrafiltration membrane as pretreatment for drinking water nanofiltration treatment: Performance, cleaning, and costs based on an engineering case - Yawei Xie; Chengyue Fan; Yichen Fang; Xiwang Zhu; Jiaming Yan; Haodong Liu; Hongyuan Liu (Journal of Cleaner Production, 2025)

A review of the pollution signatures of polycyclic aromatic hydrocarbons in the sediments of the East China Sea - Fang Yin; Chen Gao; Daolun Feng; Yawei Sun (Environmental Pollution, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Photo-Enhanced Lead-Free Antimony-Based perovskite triboelectric nanogenerator for Dual-Mode detector - Ling Ding; Zhan Wei; Na Sun; Yawei Cai; Yanhong Zhou; Kan Fang; Guigen Wang (Chemical Engineering Journal, 2024)

Histopathological, physiological, and multi-omics insights into the hepatotoxicity mechanism of nanopolystyrene and/or diclofenac in Mylopharyngodon piceus - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Jiajie Fang; Zequn Huang; Yubang Shen; Xiaowu Chen (Environmental Pollution, 2024)

Bond behavior of an ultra-high performance concrete-filled anchorage for carbon fiber-reinforced polymer tendons under static and impact loads - Yawei Fang; Zhi Fang; Lixin Feng; Yu Xiang; Xuhong Zhou (Engineering Structures, 2023)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

DLGAP1-AS2 promotes estrogen receptor signalling and confers tamoxifen resistance in breast cancer - Xiaoli Liang; Yang Zhao; Zeng Fang; Nan Shao; Duanyang Zhai; Mengmeng Zhang; Liang Yu; Yawei Shi (Molecular Biology Reports, 2022)

Neurobehavioral performance of PAH exposure in male coal miners in Shanxi, China: a cross-sectional study - Fang Wang; Liuye Yang; Bin Zhang; Gaisheng Liu; Chongjian Wang; Yawei Zhang; Tong Wang (International Archives of Occupational and Environmental Health, 2020)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Forest carbon storage and tree carbon pool dynamics under natural forest protection program in northeastern China - Yawei Wei; Dapao Yu; Bernard Joseph Lewis; Li Zhou; Wangming Zhou; Xiangmin Fang; Wei Zhao; Shengnan Wu; Limin Dai (Chinese Geographical Science, 2014)

Land use effects on soil organic carbon, microbial biomass and microbial activity in Changbai Mountains of Northeast China - Xiangmin Fang; Qingli Wang; Wangming Zhou; Wei Zhao; Yawei Wei; Lijun Niu; Limin Dai (Chinese Geographical Science, 2014)